Utro nga pagtindog narratives of women from Guiuan after Haiyan - Manalo, Lilimay R. (Philippine Sociological Review, 2015)
This article aims to provide an analysis of the narratives of survival and recovery. The Waray term "utro nga pagtindog," which literally means, "to stand up again," was used to better understand the hopes and anxieties of women in the process of recovering from distressing situations. This article also aims to show the importance of narratives in sociological research. It focused on the great loss and survival of three women Guiuananons from Eastern Samar during the onslaught of Typhoon Yolanda in 2013. From the stories told by the survivors, we were able to identify similarities as well as some recurring themes. The article argues that these common storylines contribute to the narrative of survival, likewise to that of recovery. The article also includes the relationship of the narratives to agency--showing how these women shifted from victims to survivors.